Trends in Air Temperature and Precipitation in Southeastern Czech Republic, 1961-2020 - Orság, Matěj; Fischer, Milan; Trnka, Miroslav; Brotan, Jan; Pozníková, Gabriela; Žalud, Zdeněk (Mendelova univerzita v Brně, 2022)
This study presents a summary of sixty years of air temperature and precipitation measurements at the Žabčice weather station, located in the southeastern Czech Republic and operated by Mendel University in Brno. An instrumental dataset spanning two climatological normal periods (1961-1990 and newly established 1991-2020) is analyzed for long term linear trends with monthly data presented in full span in Appendices. In the new climate normal period, the mean annual temperature increased from 9.3 oC to 10.3 oC with growing trend of 0.34 oC/10 years (p < 0.001). Every calendar month of year is warmer, with the highest and fastest increase in August (+2.0 oC, 0.64 oC/10 years, p < 0.001) and the lowest in October (+0.2 oC). Annual precipitation sum increased negligibly (+11.1 mm), however, the quarterly distribution significantly changes towards drier second quarter (-22.9 mm, p < 0.05) and wetter third quarter (+37.1 mm, p < 0.05). Number of tropical days (maximum daily air temperature > 30 oC) significantly increased (+4.44/10 years, p < 0.001), whereas number of frost days is negligibly decreasing (-0.88/10 years). Temperature derived Huglin index for vineyards increased by 369 oC to a seasonal sum 2062 oC (+84 oC/10 years, p < 0.001). This study provides evidence of the rate of changing climate at this southern Moravia lowland site.
Keywords: air temperature; climate change; climatological normal; long-term trend; Moravia; precipitation; Žabčice